INTEGRASI PENDIDIKAN IPS DALAM PEMBELAJARAN UNTUK MENGEMBANGKAN SOFT SKILL SISWA DI SEKOLAH DASAR AL-GONTORY TAMANAN TULUNGAGUNG - Nor Nas Kurnia Nanisanti (STKIP PGRI Tulungagung, 2017)
Abstract: Education is a process of humanizing. To achieve the full human dignity is impossible without going through the process of education. Education must be able to produce people who had precious characters, in addition to having academic abilities and skills are adequate. One way to realize the human character is to integrate character education into every lesson. The integration of character education in learning can be done by loading the values of characters in all the subjects taught in schools and in the implementation of learning activities. The teacher must prepare for character education from the planning, implementation and evaluation. Implementation of character education in schools should be supported by exemplary teachers and parents as well as cultural character.Â Key Words:Integration, Character Education, Social Learning, Soft Skills Developing